Islam and the Orientalists - Abdullah, Fatimah (Intellectual Discourse, 2004)
The term Islam has been used in various ways, i.e., (a) as submission, (b) as definition of religion and, (c) as the name of a particular religion. However, some orientalists erroneously argue that the term Islām is not the name of a particular religion and thus they try to confuse true tawḥīd with shirk. Both orientalists and supporters of the modern concept of transcendent unity of religions have skillfully used it to confuse Muslims and other readers.